The Influence of the Track Parameters on Vibration Characteristics of Subway Tunnel - Wenbo Shi; Linchang Miao; Junhui Luo; Honglei Zhang (Shock and Vibration)
In soft soil areas, such as the Nanjing, it is very important to quantitatively analyze the dynamic behaviors of soft soils during the metro train operation. A nonlinear coupling model of wheel-track and a finite element calculation model of tunnel and soil were established based on the mechanical character of elastic supporting block ballastless track and the actual parameters of Nanjing soft soil. The time-variant vertical acceleration of the rail, the sleepers, and the surface of the tunnel can be calculated by the models, and the frequency dependence acceleration was verified by the fast Fourier transform algorithm. A modified vibration power level for human sensitivity was used to quantify the vibration energy of each part of the system, and the impact of the parameters in the model was evaluated. The results can be applied to the metro design and construction, which also can be the guidance during the tunnel construction.